Anticipating extinctions of glacial relict populations in mountain refugia. (September 2016) - Jiménez-Alfaro, Borja; García-Calvo, Laura; García, Pedro; Acebes, José Luis
Abstract: Glacial relict populations at the rear-edge of species' distributions are expected to respond dramatically to climate warming, yet very few studies have compared their conservation status in current refugia. Here we combine population genetics with species distribution modelling to assess patterns and causes of extinction or persistence in two cold-adapted species, Salix hastata and Juncus balticus, which survived post-glacial retractions in calcareous fens of the Iberian Peninsula. In both species, we detected extremely-low genetic diversity and clonal strategies in red-listed populations of the most marginal region (Cantabrian Range), but high genetic diversity linked with sexual reproduction in populations from a less marginal region of the rear edge (Pyrenees). Genetic patterns were partially explained by past and present species´ climatic niches, more remarkably in the arctic-alpine S . hastata than in the boreo-atlantic J . balticus, suggesting different biogeographic history but similar sensitivity to global change. Our results show different magnitudes of extinction debt in regional populations that have survived in mountain refugia since the Last Glacial Maximum. Functional extinction of the most marginal populations can be explained by postglacial climate change and the historical decline of mire habitats. In contrast with the current trend of predicting future effects of climate change, we highlight that glacial relict populations might be currently going into extinction in climatically marginal regions. These populations can provide valuable information about the processes involved in species extinctions, improving our capacity to anticipate the effect of global change across regions and habitats. Graphical abstract: Highlights: We assessed symptoms of extinction in glacial relict populations of two mire species. Population genetic diversity was extremely low in the most marginal populations. The results were congruent with past and current climatic niches. Our results support upcoming extinctions of glacial relicts at rear edge distributions. More efforts are needed to anticipate regional extinctions in mountain refugia.